Assessing travelers' characteristics and trip information influencing the boarding and alighting experience at bus stops in a developing urban city: a simultaneous bivariate ordered probit approach. Issue 3 (September 2022) - Ibrahim, K.B.M.; Haque, Tashdid; Tanim, Md Fardeen; Raihan, Md Asif; Hossain, Moinul
Highlights: Travelers' characteristics and trip information influencing the boarding and alighting experience at bus stops. Simultaneous bivariate ordered probit model assessing the effect of the explanatory variables. Income, education level, occupation, vehicle ownership, travel day, frequency of the particular trip, purpose of the trip, pedestrian facilities, availability of feeder services have significant impacts on boarding and alighting experience. Multi-modal integration considering the feeder services in the system will improve the ease of accessibility for passengers. Abstract: Improved public transport accessibility for the catchment area is crucial towards achieving increased transit ridership. It is essential to comprehend how passengers commute to various bus stops, how their preferences differ depending on their characteristics, and passenger's perception of prevailing commuting infrastructure to get to the bus stops. A simultaneous bivariate ordered probit model is performed in this research utilizing 2532 responses collected from a face-to-face survey at different bus stops in Dhaka, a developing urban city. The study identified socio-economic characteristics, such as income, education level, occupation, vehicle ownership; trip characteristics, such as travel day, frequency of the particular trip, purpose of the trip; and commuting facility ratings, such as pedestrian facilities, availability of feeder services to have significant impacts on either the boarding experience or the alighting experience, or both. Therefore, passenger waiting time at bus stops, walking time from origin to bus stop, pedestrian facilities, and the availability of feeder services should be addressed while developing the transport policies. Optimizing location of the bus stops would minimize passengers walking time to access the bus stop. The pedestrian facilities should be integrated with the public transportation systems. Moreover, multi-modal integration considering the feeder services in the system, leading to and from the public transport catchment area, will improve the ease of accessibility for passengers, subsequently resulting in better transit ridership. In addition, passengers' boarding experiences were found to influence their alighting experiences. The effect of the explanatory variables found in this study can help policy-makers and transit agencies formulate effective policy countermeasures to mitigate and improve the variables affecting public bus ridership in a developing urban society.